(untitled) (Journal of Parents and Teachers, 1996)
The document addresses education in the context of health and sustainability, highlighting the importance of cross-cutting activities and comprehensive education. Mention is made of the need to prepare students to participate responsibly in society. In addition, reference is made to the implementation of educational proposals under the LOGSE framework.